2022
DOI: 10.1097/htr.0000000000000754
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neuroinflammation in Neuropsychiatric Disorders Following Traumatic Brain Injury: A Systematic Review

Abstract: Background: Neuropsychiatric symptoms are common following traumatic brain injury (TBI), but their etiological onset remains unclear. Mental health research implicates neuroinflammation in the development of psychiatric disorders. The presence of neuroinflammatory responses after TBI thus prompts an investigation of their involvement in the emergence of neuropsychiatric disorders postinjury. Objective: Review the literature surrounding the role of neuroinflammation and immune response post-TBI in the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
(304 reference statements)
0
6
0
Order By: Relevance
“…A limitation to this study was that we did not study inflammation and neurodegeneration, which play an important role in the development of depression, anxiety, and other neuropsychiatric complications of TBI [ 68 ]. The pathogenesis of post-TBI neuropsychiatric disorders is complex and multifactorial [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation to this study was that we did not study inflammation and neurodegeneration, which play an important role in the development of depression, anxiety, and other neuropsychiatric complications of TBI [ 68 ]. The pathogenesis of post-TBI neuropsychiatric disorders is complex and multifactorial [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…TB is characterized by an excessive systemic inflammatory response [ 38 ]. Systemic inflammation produces neuroinflammation and neuronal damage caused by oxidative stress and activating microglia that impair cognitive function, including learning and memory, and can contribute to neurobehavioral changes, including the development of neuropsychiatric disorders [ 39 , 40 , 41 ]. In the absence of brain bacteria, we have shown that Mtb lung infection caused neuroinflammation and behavioral impairments [ 25 ], and similar results have been described in Mycobacterium lepraemurium [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these frequent long-term consequences of traumatic injuries share neuroinflammation among key pathophysiological mechanisms [58,[127][128][129]. According to a recent systematic review [130], the presence of depressive and/or anxiety symptoms in TBI samples was found to be associated with higher concentrations of serum and CSF, CRP, CSF-derived markers of sVCAM-1, sICAM-1, and sFAS, and IL-10, IL-8, IL-6, and TNF-α. Acute measures of some of these biomarkers predicted the onset of depression at 6 and 12 months post-injury.…”
Section: Neuroinflammation and Other Neuropsychiatric Outcomes In The...mentioning
confidence: 99%